Influence of age and gender on oral health impact profile among dental implant patients in alkarkh district in Baghdad / Iraq: cross-sectional study - Modar Abdul Abbas Fedik,; Ban Sahib Diab, (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the age and gender influence on the quality of life of patients with a dental implant. Methods: The cross-sectional study was conducted from February to April 2022 at Al-Mammon Specialised Dental Centre in the Al-Karkh sector of Baghdad, Iraq, and comprised healthy adult subjects of either gender who had dental implant treatment in the preceding 2 years and their dental implant was in place for at least 6 months. . Data was collected using the Oral Health Impact Profile Questionnaire to measure oral health quality of life. Data was analysed using SPSS 22. Results: Of the 103 subjects, 55(53.4%) were females and 48(46.6%) were males. There were 41(39.81%) subjects aged 18-37 years, 42(40.78%) aged 37-56 years and 20(19.42%) aged 57-74 years. Of the total, 50(48.5%) subjects had moderate health quality, followed by 26(25.24%) low and 27(26.21%) high. There was a significant association of age and gender on the quality of life (p<0.05). Conclusion: Age and gender were found to be important factors influencing the quality of life of dental implant patients. Key Words: Quality of life, Oral health impact profile, Dental implant patient.